Performance of South African children on the Communication and Symbolic Behavior Scales—Developmental Profile (CSBS DP). Issue 3 (6th November 2015) - Chambers, Nola; Stronach, Sheri T.; Wetherby, Amy M.
Abstract: Background: Substantial development in social communication skills occurs in the first two years of life. Growth should be evident in sharing emotion and eye gaze; rate of communication, communicating for a variety of functions; using gestures, sounds and words; understanding language, and using functional and pretend actions with objects in play. A delay in these early social communication skills may be the first sign of a developmental delay in young children in nearly all categories of disabilities—including specific language impairment, autism spectrum disorder, HIV/AIDS, lack of environmental stimulation or institutionalization, and global developmental delays—and early detection of these delays is critical for enrolment in appropriate early intervention services. Aims: No standardized tests of early social communication skills exist for very young children in South Africa (SA). An existing evaluation tool that has the potential to be culturally fair for children from cultural backgrounds different to the standardization group is the Communication and Symbolic Behaviour Scales—Developmental Profile (CSBS DP). This study aimed to document the performance of a group of English‐speaking SA children ranging in age from 12 to 24 months on the CSBS DP and to compare this performance with the original standardization sample. Methods & Procedures: Sixty‐seven English‐speaking SA children from a range of cultural and linguistic backgrounds were assessed on the CSBS DP Behaviour Sample. Group scores were compared with the original standardization sample using inferential statistics. Outcomes & Results: The results provide preliminary support for the suitability and validity of the face‐to‐face Behaviour Sample as a measure of early social communication skills in this sample of English‐speaking SA children from a range of cultural groups between 12 and 24 months of age. Conclusions & Implications: While further research in the SA population is needed, these findings are a first step towards validating a culturally appropriate measure for early detection of social communication delays in a sample of SA toddlers.